Beyond Recommendations: Strategic Recruitment Models for High-Quality Islamic Education - Candra Ferdian Saputra; Fadlillah Fadlillah; Summiyani Summiyani (JURNAL AL-TANZIM, 2026)
This study aims to analyze the management of teacher recruitment and selection to improve the quality of educators in integrated Islamic schools. This research stems from the gap between formal recruitment policies and actual implementation, particularly regarding recommendation-based recruitment practices and teacher placements that do not fully align with academic competencies. The study used a qualitative approach with a descriptive design. Subjects included principals, vice-principals, and teaching staff. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the recruitment process is implemented through needs analysis, publication of vacancy information, administrative selection, Quran reading tests, and interviews. However, several obstacles remain, such as suboptimal recruitment transparency, incompletely standardized selection procedures, and mismatched teaching placements with expertise. These findings highlight the importance of strengthening transparency, standardizing selection, implementing microteaching, and continuing professional development to produce competent educators aligned with the vision of integrated Islamic education.